Safety, Tolerability, and Pharmacokinetics of SMT C1100, a 2-Arylbenzoxazole Utrophin Modulator, following Single- and Multiple-Dose Administration to Pediatric Patients with Duchenne Muscular Dystrophy. - Valeria Ricotti; Stefan Spinty; Helen Roper; Imelda Hughes; Bina Tejura; Neil Robinson; Gary Layton; Kay Davies; Francesco Muntoni; Jonathon Tinsley (PLoS ONE, 2016)
Purpose SMT C1100 is a utrophin modulator being evaluated as a treatment for Duchenne muscular dystrophy (DMD). This study, the first in pediatric DMD patients, reports the safety, tolerability and PK parameters of single and multiple doses of SMT C1100, as well as analyze potential biomarkers of muscle damage. Methods This multicenter, Phase 1 study enrolled 12 patients, divided equally into three groups (A-C). Group A were given 50 mg/kg on Days 1 and 11, and 50 mg/kg bid on Days 2 to 10. Group B and C received 100 mg/kg on Days 1 and 11; Group B and Group C were given 100 mg/kg bid and 100 mg/kg tid, respectively, on Days 2 to 10. A safety review was performed on all patients following the single dose and there was at least 2 weeks between each dose escalation, for safety and PK review. Adverse events (AEs) were monitored throughout the study. Results Most patients experienced mild AEs and there were no serious AEs. Two patients required analgesia for pain (headache, ear pain and toothache). One patient experienced moderate psychiatric AEs (abnormal behaviour and mood swings). Plasma concentrations of SMT C1100 at Days 1 and 11 indicated a high degree of patient variability regardless of dose. Unexpectedly the SMT C1100 levels were significantly lower than similar doses administered to healthy volunteers in an earlier clinical study. In general, individual baseline changes of creatine phosphokinase, alanine aminotransferase, aspartate aminotransferase levels fell with SMT C1100 dosing. Conclusions SMT C1100 was well tolerated in pediatric DMD patients. Trial registration ClinicalTrials.gov NCT02383511.